A Cross-Country Analysis of the Tax-Push Hypothesis - Padoa-Schioppa, Fiorella (IMF Working Papers; Working Paper, 1992)
This paper presents a microeconomic theoretical model of union optimizing behavior which is then used to test the relevance of the tax-push hypothesis for wage formation in nine Western European countries. Two factors-the compensation and the progressivity effects-are shown by the model to account for the effect (if any) of tax rates on wage formation. A wage equation tested for the period 1960-1988 shows that in general small open economies have negligible compensation and progressivity effects, while in larger economies direct, indirect and social security tax rates are transferred onto the real labor cost. All countries show a weakening of the tax shifting starting at the end of the 1970s or the beginning of the 1980s.